Advances in quantum secure direct communication. Issue 2 (4th May 2021) - Zawadzki, Piotr
Abstract: The practical implementation of quantum secure direct communication (QSDC) will undoubtedly be a milestone in the development of quantum cryptography. Research is in its final phase and focuses on developing secure protocols that consider realistic constraints and are feasible within the current state of technology. Three well‐known protocols ae compared, Ping‐Pong, Two‐Step and Deng‐Long, in the context of the level of security offered and the challenges related to their implementation. This work explains how the evolution of QSDC protocols from a purely quantum formulation to hybrid classical‐quantum solutions based on the Wyner wiretap channel model can solve most problems encountered. The work aims to inform scientists in other fields of quantum information processing about the latest advances in QSDC. The attached appendix introduces basic concepts for readers unfamiliar with this research area.